ANALISIS TRADING VOLUME ACTIVITY PADA PERISTIWA POLITIK SEBELUM DAN SESUDAH DEMO DPR (EVENT STUDY PADA INDEKS SAHAM LQ45) - Yupuria, Ghea; Saranga, Laudia Vika; Saputri, Septi; Wibowo, Agus Satrya; Yuniati, Ade (E-Jurnal Akuntansi TSM, 2025)
The DPR demonstration event triggered reactions in the stock market, particularly in terms of trading volume activity. This study aims to analyze the difference in trading volume activity during the 2025 DPR demonstration political event. The research method is quantitative based on event study with SPSS analysis tools. The sample used in this study is all companies listed in LQ45. The research period was conducted for 10 days before and 10 days after the DPR demonstration event. The analysis technique used the Wilcoxon signed ranks test. The results of this study indicate that there is no significant difference in trading volume activity for LQ45 stocks before and after the 2025 DPR Demonstration. These findings show that information about the 2025 DPR Demonstration did not produce negative or positive signals, thus having no impact on changes in transaction intensity. The implications of these findings indicate that not all political events or social issues automatically have a significant impact on market activity.